2019
DOI: 10.1111/aogs.13664
|View full text |Cite
|
Sign up to set email alerts
|

Do female age and body weight modify the effect of individualized FSH dosing in IVF/ICSI treatment? A secondary analysis of the OPTIMIST trial

Abstract: Introduction The OPTIMIST trial revealed that for women starting in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) treatment, no substantial differences exist in first cycle and cumulative live birth rates between an antral follicle count (AFC)‐based individualized follicle‐stimulating hormone (FSH) dose and a standard dose. Female age and body weight have been suggested to cause heterogeneity in the effect of FSH dose individualization. The objective of the current study is to evaluate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, the pharmacokinetics and pharmacodynamics of Gn should be individualized to different patients. The excess weight affects the ovarian response to Gn and exogenous serum FSH level is inversely associated with body weight (24). The volume of extracellular fluid is a key factor for drug distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pharmacokinetics and pharmacodynamics of Gn should be individualized to different patients. The excess weight affects the ovarian response to Gn and exogenous serum FSH level is inversely associated with body weight (24). The volume of extracellular fluid is a key factor for drug distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, body weight is more predominant in determining FSH distribution than BMI (25). A previous study found that reducing the FSH dose in predicted hyper responders with body weight > 55kg significantly decreased the OHSS occurrence but also decreased the probability of live birth (24). On the contrary, a randomized controlled trial (RCT) found that the reduction of Gn dosage significantly lowered the OHSS incidence, together with no influence on live birth rates (11).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, body weight is more predominant in determining FSH distribution than BMI [30]. A previous study found that reducing the FSH dose in predicted hyper responders with body weight > 55kg signi cantly decreased the OHSS occurrence but also decreased the probability of live birth [29]. On the contrary, a randomized controlled trial (RCT) found that reduction of Gn dosage signi cantly lowered the OHSS incidence, together with no in uence on live birth rates [16].…”
Section: Discussionmentioning
confidence: 99%
“…The excess weight affects the ovarian response to Gn [28]. Exogenous serum FSH level is inversely associated with body weight [29]. The volume of extracellular uid is a key factor in drug distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Poor ovarian response leads to a high risk of treatment cycles being canceled or a lack of high-quality embryos for transfer. Studies have demonstrated that the impact features, e.g., a women’s clinical information (age, body mass index (BMI), infertility cause, and infertility duration), basal endocrine level (Anti-Müllerian hormone (AMH), basal follicle stimulating hormone (bFSH)), and ultrasound-related index (antral follicle count (AFC)), are closely related to the extent of ovarian response to COS [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The features, such as age, AMH, bFSH, and AFC, etc., are currently recognized as high-impact features related to ovarian reserve function [ 10 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%